A holistic approach to sustain and support lifelong practices of wellness among healthcare professionals: generating preliminary solid steps towards a culture of wellness - Beverley Argus-Calvo; Deborah J. Clegg; Maureen D. Francis; Alok Kumar Dwivedi; Paul A. Carrola; Marie Leiner (BMC Medical Education)
Abstract Background The COVID-19 pandemic has served as a catalyst for recognizing the challenging environments in which healthcare workers operate, underscoring the urgent need to enhance their wellness to better support themselves and others. The implementation of a culture of wellness within the context of healthcare education, with a particular emphasis on individual-level strategies, allows for the realization of its intrinsic value and significance as a foundation for broader organizational strategies. This approach facilitates the establishment of a sustainable culture of wellness that benefits both current and subsequent generations of healthcare professionals. Methods We implemented our wellness program using a pragmatic pre-post study design for different settings. Our wellness intervention program was tested in three ways by creating combinations of different intensities (high, moderate, or low), delivery methods (face-to-face vs. virtual), different motivations (incentive, mandatory, or volunteer participation), and different timings (during medical programs or before entering into healthcare programs) among medical and nursing students. The effects of the wellness program were measured on quality of life, emotional intelligence, and efficacy scores among healthcare students. Statistical methods included repeated measures analysis of variance and paired t-tests. Results A total of 224 students (13 in high, 145 in moderate, and 66 in low-dose interventions) participated in our study program. Most scores were significantly improved except for a few factors in the high-dose face-to-face Well-Teach intervention cohort. Among quality of life components, the average psychological scores were markedly increased after high (13.2 vs. 14.7, p = .018), moderate (13.9 vs. 14.8, p < .001), and low (12.8 vs. 13.4, p < .001) intensity intervention cohorts. The moderate and low intensity of wellness intervention cohorts had the highest impact on the total emotional intelligence scores (mean difference = 3.021, 95%CI:0.553–5.488, p = .008) and (mean difference = 5.197, 95%CI:3.057–7.337, p = < 0.001), respectively. The low-dose healthcare intervention program yielded improvements in all components of all scores to a greater extent than moderate-dose or high-dose with face-to-face intervention programs. Conclusions This study demonstrates that our multifaceted Well-Teach model can be used to improve the quality of life, emotional intelligence, and self-efficacy of healthcare students. Low- or moderate-intensity intervention programs integrated into the curriculum may be more practical in health sciences education to sustain and promote lifelong wellness practices as solid steps toward attaining a “culture of wellness”. Our model should be considered to be beneficial, sustainable, cost-effective, comprehensive, and effective for current and future generations of healthcare providers.